Determination of Sustainable Supply Chain Strategy in Natural Gas Transition as a Substitute for Subsidized Household LPG Using FAHP and TOPSIS Method - Avriska Padmasari; Isna Nugraha (EPI International Journal of Engineering, 2025)
The high dependency on subsidized LPG imports and the increasing demand for cleaner energy encourage the utilization of natural gas as an alternative household energy source in Indonesia. This study aims to determine the most appropriate sustainable supply chain strategy in supporting the transition of natural gas as a substitute for subsidized household LPG at Company XYZ. The research applies a Multi-Criteria Decision Making approach using Fuzzy Analytical Hierarchy Process (FAHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). FAHP is used to determine the weight of criteria based on economic, environmental, and social aspects, while TOPSIS is applied to rank the alternative strategies. The results indicate that the strategy of infrastructure integration and gas distribution efficiency achieved the highest preference value of 0.9712, making it the most recommended strategy. The selected strategy is considered capable of improving distribution efficiency, expanding household gas network utilization, and reducing dependency on subsidized LPG. Therefore, the implementation of sustainable supply chain management in the gas sector can support energy transition and improve the effectiveness of household gas distribution systems.